Identification and validation of differentially expressed genes in allergic asthma pathogenesis using whole-transcriptome sequencing - Cui, Fang; Liu, Rui; Wang, Li; He, Jing; Xu, Yanxia (Frontiers in Medicine, 2025)
ObjectiveThis study aims to systematically identify differential gene expression profiles in patients with allergic asthma through whole-transcriptome sequencing and validate the role of these genes in asthma pathogenesis, thereby uncovering potential molecular mechanisms.MethodsThis study recruited a cohort of 80 individuals diagnosed with allergic asthma and 40 healthy controls. RNA was extracted from both peripheral blood and airway samples, and sequencing was performed using the Illumina NovaSeq 6000 platform. Potential differential genes were confirmed through three independent techniques to validate the findings: quantitative reverse transcription polymerase chain reaction (qRT-PCR), immunohistochemistry, and Western blot analysis. Differential gene expression was analyzed using DESeq2 software, providing a rigorous statistical framework for RNA-Seq data interpretation. Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were employed to elucidate the biological significance of the differentially expressed genes, offering insights into the molecular mechanisms underlying allergic asthma.ResultsDifferential expression analysis identified multiple genes with significant differences between the patient and control groups. Inflammatory-related genes such as IL1B, CCL17, and MUC5AC were significantly upregulated in the patient group (p < 0.05), while regulatory immune factors such as FOXP3 and IFNG showed significantly higher expression in the control group (p < 0.05). Functional enrichment analysis indicated that the differential genes were mainly enriched in immune response, T-cell activation, and MAPK signaling pathways. Experimental validation demonstrated consistency between transcriptomic data and RNA and protein expression levels, further supporting the involvement of these genes in asthma.ConclusionDifferential gene expression profiles play a crucial role in the pathogenesis of asthma. This study provides important evidence for understanding the molecular mechanisms of asthma and developing novel targeted therapeutic strategies.